DOI: 10.32657/10356/136540
|View full text |Cite
|
Sign up to set email alerts
|

A methodology to design multimodal public transit networks : procedures and applications

Abstract: Throughout my stay at TUMCREATE, I came across, some of the most intelligent, kind-hearted and encouraging people. They have touched my life in so many ways, that I would not have been able to do this without their support.Firstly, I would like to express my gratitude to Dr. Andreas Rau who believed in me and supported me for so many years through my stay at TUMCREATE. Secondly, I would like to thank Prof. Fritz Busch, whose continuous support and pragmatic view about research helped me to broaden my vision. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
(92 reference statements)
0
0
0
Order By: Relevance
“…It was claimed that the bus network architecture intends to determine the capacities of the routes based on the total number of prospective boarding passengers without limitation. Moreover, it has been shown that capacity-free assigning algorithms are convenient and rapid in complex systems [62,63].…”
Section: Introductionmentioning
confidence: 99%
“…It was claimed that the bus network architecture intends to determine the capacities of the routes based on the total number of prospective boarding passengers without limitation. Moreover, it has been shown that capacity-free assigning algorithms are convenient and rapid in complex systems [62,63].…”
Section: Introductionmentioning
confidence: 99%